Electric–dielectric properties and complex impedance analysis of La0.5Ca0.5−xAgxMnO3 manganites. Issue 3 (5th December 2014) - Smari, M.; Rahmouni, H.; Elghoul, N.; Walha, I.; Dhahri, E.; Khirouni, K.
Abstract : The electric and dielectric properties of La0.5 Ca0.5− x Ag x MnO3 (LCMO–Ag with x = 0 and x = 0.4) were investigated using the impedance spectroscopy technique. Abstract : The electric and dielectric properties of La0.5 Ca0.5− x Ag x MnO3 (LCMO–Ag with x = 0 and x = 0.4) were investigated using the impedance spectroscopy technique. For the free compound, conductivity analysis proved the absence of a metal–semiconductor transition in the temperature range of 80 K to 700 K. When silver was introduced, such transition appears at around T MS = 200 K. We found that the conduction mechanism was governed by small polaron hopping (SPH) in the high temperature region and by variable range hopping (VRH) in the low temperature region. Several results were deduced from the complex impedance analysis (CIA). First, a non-Debye relaxation phenomenon in the system was observed. Second, the CIA permitted us to model the compounds in terms of an electrical equivalent circuit. Moreover, this study confirmed the contribution of the grain boundary in the transport properties. It was found that the activation energy deduced from the conductivity, the relaxation time and the grain boundary were close to each other. The dielectric constant and dielectric loss were investigated. For the free compound, the dielectric transition was not observed in the investigated temperature range but, for the doped compound, the dielectric transition appeared at T d = 200 K. The T d value was close to the T MS value. The thermal evolution of the real part of dielectric permittivity is described by the Curie–Weiss law. From the variation of the imaginary part of the dielectric permittivity and the dielectric loss versus temperature at different frequencies, we found that the free compound had a typical behavior of a relaxor but the doped one had a typical behavior of a normal dielectric.